Perspectives on geospatial information science education: an example of urban planners in Southern Africa. Issue 2 (3rd April 2017) - Musakwa, Walter
Abstract: Since the introduction of geographic information systems (GIS) in the 1960s, it has evolved tremendously to an extent that it permeates our daily lives. Initially, GIS usage started in the developed countries and now increasingly filtered to developing countries. The town planning profession was one of the early adopters of GIS. Geospatial information is a useful source of data that is needed in urban planning. In these days of the New Urban Agenda 2030, smart cities are even more required from planners in using geospatial information to face urban challenges such as sustainable urban development and climate change. Although GIS has promised a lot for urban planning, it has not reached its full potential. Moreover, many studies have focused on developed countries with limited studies on geospatial information application in municipalities and GIS education from a perspective of developing countries. In this study, a survey on the usage of geospatial information science (GSIS) in two cities, namely Bulawayo in Zimbabwe and Ekurhuleni in South Africa, was conducted, and an overview of the state of GIS curricula in planning schools is discussed. The results indicate that considerable progress has been made in the application of geospatial information in municipal planning; however, there are impediments limiting the full utilization of geospatial information in local municipalities. These impediments include: inadequate GIS curricula in planning schools, lack of resources, and lack of political will. These challenges manifest differently in well-resourced municipalities and those with limited resources. The study proposes planning-relevant GIS curricula to improve the level of GIS use in planning practice.